Cystoliths of Parietaria judaica can serve as an internal source of CO2 for photosynthetic assimilation when stomata are closed. (7th July 2019) - Giannopoulos, Andreas; Nikolopoulos, Dimosthenis; Bresta, Panagiota; Samantas, Aris; Reppa, Chrysavgi; Karaboiki, Kalliopi; Dotsika, Elissavet; Fasseas, Constantinos; Liakopoulos, Georgios; Karabourniotis, George
Abstract : Under certain conditions, leaf cystoliths of Parietaria judaica can decompose, and the CO2 released can be photosynthetically assimilated. This process lowers surplus energy and protects the photosynthetic apparatus. Abstract: The recently reported 'alarm photosynthesis' acts as a biochemical process that assimilates CO2 derived from the decomposition of calcium oxalate crystals. This study examined whether CaCO3 cystoliths could also serve as CO2 pools, fulfilling a similar role. Shoots of Parietaria judaica were subjected to carbon starvation, abscisic acid (ABA), or bicarbonate treatments, and the volume of cystoliths and the photochemical parameters of photosystem II (PSII) were determined. The size of cystoliths was reduced under carbon starvation or ABA treatments, whereas it was restored by xylem-provided bicarbonate. Under carbon starvation, ABA, or bicarbonate treatments, the photochemical efficiency of PSII was higher, while non-photochemical quenching, representing the safe dissipation of excess PSII energy due to lack of electron sinks, was lower in treated samples compared with controls. This observation suggests the involvement of ABA or other carbon starvation cues in the release of subsidiary CO2 for photosynthesis, inevitably from an internal source, which could be the cystoliths. Carbon remobilized from cystoliths can be photosynthetically assimilated, thus acting as a safety valve under stress. Together with alarm photosynthesis, these results show a tight link between leaf carbon deposits and photosynthesis.